A study on the effectiveness of coping with test anxiety program based on cognitive-behavioral approach - Fulya Türk; Ayşe Nur Katmer (International Journal of Evaluation and Research in Education (IJERE), 2019)
The purpose of this study is to examine the impact of the program for coping with test anxiety based on the cognitive-behavioral approach on the levels of test anxiety, irrational thoughts, coping levels and academic self-efficacy perceptions of adolescents in the 8th grade. The study was performed as a semi-experimental study based on pre-test and post-test model with an experimental group and a control group. There were 32 students studying in the 8th grade in Kilis during the 2018-2019 school year participated in the study. While a seven-session Coping with Test Anxiety program based on Cognitive-Behavioral approach was applied to the students in the experimental group, no study was conducted with the control group. The Mann-Whitney U Test, Friedman Test, and Wilcoxon Signed-Rank Test were used in the analyses of data obtained from the study. According to study results, it can be said that the program for coping with test anxiety based on the cognitive-behavioral approach was significantly effective in the levels of test anxiety, irrational beliefs and active and avoidant coping levels of the adolescents while it was not effective in academic self-efficacy perceptions and negative avoidant coping levels.